Representasi Etnopedagogi dan Pendidikan Inklusi dalam Novel Totto-chan: Gadis Cilik di Jendela Karya Tetsuko Kuroyanagi - Afina Damayanti; Khalidatun Nuzula; Hani Atus Solikhah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research focuses on analyzing ethnopedagogical values and inclusive education practices in the novel Totto-chan: Gadis Cilik di Jendela. This study was also enriched by the results of the researcher's observations during teaching practice in inclusive public schools. This research uses a descriptive qualitative approach with the content analysis method of the Harold D. Lasswell model by giving symbols and then interpreting them. Lasswell model by giving symbols and then interpreting them. Based on the results of the analysis, 8 data findings were found, consisting of 4 ethnopedagogical data and 4 data on inclusive education practices. The findings show that the novel can be a reflective medium and a source of inspiration in building inclusive schools that are humanist, adaptive, and rooted in local values.